The Effect of Neoadjuvant Chemotherapy on Lymph Node Metastasis of FIGO Stage IB1-IIB Cervical Cancer: A Systematic Review and Meta-Analysis - Chen, Bingxin; Wang, Liming; Ren, Ci; Shen, Hui; Ding, Wencheng; Zhu, Da; Mao, Lu; Wang, Hui (Frontiers in Oncology, 2020)
Abstract Objectives This study aimed to assess the effect of NACT on the rate of LNM in FIGO stage IB1-IIB cervical cancer patients and compare the LNM between NACT plus surgery and surgery only. Methods We identified 34 eligible studies in PubMed, Web of Science, Cochrane Library and EMBASE from inception to July 27, 2019. Data analyses were performed by Stata (version 13) and Revman (version 5.3). Results In these included 34 studies, the pooled incidence of LNM was estimate as 23% (95% CI, 0.20-0.26; I2=79.6%, P<0.001). In the subgroup analysis, we identified five factors, including study type, year of publication, continents that patients came from, histological type and the FIGO stage. When taking FIGO stage into consideration, the LNM rate was 13% in stage IB (95% CI: 0.10-0.15; I2=5.5%, P=0.385), 23% in stage IIA (95% CI: 0.18-0.28; I2=0%, P=0.622), and 27% in stage IIB (95%CI: 0.20-0.33; I2=0%, P=0.898), respectively. And through the comparison between NACT plus surgery and surgery only based on the six RCTs, the incidence of positive lymph nodes was lower in patients receiving NACT plus surgery than surgery only (RR=0.57, 95% CI: 0.39-0.83; I2=60.5%, P=0.027). Conclusions Among cervical cancer in stage IB1-IIB, the preoperative neoadjuvant chemotherapy plus radical surgery resulted in a 23% probability of lymph node metastasis, which was lower than those receiving radical surgery only. In the stage IIA and IIB, the effect of NACT to reduce LNM was more obvious.